2015
DOI: 10.21275/v4i12.nov151940
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Organizational Learning Culture to Organizational Citizenship Behavior toward Knowledge Sharing Behavior

Abstract: This research was conducted to examine the role of organizational learning culture in moderating of OCB on knowledge sharing behavior. It was based on survey of 100 community facilitators. Structural equation modeling was used to test the hypothesis. The results showed that OCB had a significant effect on knowledge sharing behavior, but this correlation was weak. It was also found that Organizational learning culture as a strong significant moderator of OCB toward knowledge sharing behavior. Sportmanship to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The knowledge management system is the main determinant of the knowledge sharing process in an organization. OCB turns out to have a relationship or influence on KSB as empirically shown by the results of research: Jo and Joo [2]; Islam et al [3]; Susanti and Wimbarti [9], Husain et al [4]; and Sadegh [10] who concluded that OCB has a significant effect on KSB. Hypothesis 3: OCB has a significant effect on the KSB of teachers at SMAN in Surabaya Figure 1 depicts the conceptual framework proposed in this study based on the previously described background.…”
Section: Psychographic Relationship Between Ocb and Ksbmentioning
confidence: 99%
See 2 more Smart Citations
“…The knowledge management system is the main determinant of the knowledge sharing process in an organization. OCB turns out to have a relationship or influence on KSB as empirically shown by the results of research: Jo and Joo [2]; Islam et al [3]; Susanti and Wimbarti [9], Husain et al [4]; and Sadegh [10] who concluded that OCB has a significant effect on KSB. Hypothesis 3: OCB has a significant effect on the KSB of teachers at SMAN in Surabaya Figure 1 depicts the conceptual framework proposed in this study based on the previously described background.…”
Section: Psychographic Relationship Between Ocb and Ksbmentioning
confidence: 99%
“…The same thing also happens to members of the organization with all their values, beliefs, and behavior, which then creates organizational culture. Organizational learning culture (OLC) appears to have a relationship or influence on organizational citizenship behavior (OCB), as empirically demonstrated by the findings of Jo and Joo [2], Islam et al [3], Husayn et al [4], and Rini et al [5].…”
Section: The Relationship Of Olc With Ocb and Ksbmentioning
confidence: 99%
See 1 more Smart Citation